1975
DOI: 10.1007/bf00388963
|View full text |Cite
|
Sign up to set email alerts
|

The control of NAD specific malic enzyme from cauliflower bud mitochondria by metabolites

Abstract: NAD malic enzyme (EC. 1.1.1.39) has been purified from cauliflower (Brassica oleracea. var. botrytis) bud mitochondria. The enzyme exhibits complex regulatory properties being activated by a variety of metabolites including glycolytic intermediates, CoA, sulphate and Krebs cycle acids-the tricarboxylic acids with the exception of citrate being more effective than dicarboxylic acids. Fructose diphosphate which is a positive effector of the enzyme increases the affinity of the enzyme for L-malate.The enzyme is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

1976
1976
1995
1995

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…The mol wt of this form is in close accord with the reported mol wt of NAD malic enzyme isolated from animal sources (7,12). Mol wt of approximately 300,000 to 400,000 have been reported for impure preparations of NAD malic enzyme from plant tissues (4,10,14). As we also find that the purified NAD malic enzyme from potato can exist in a higher mol wt form (477,000 D) it would seem that the plant NAD malic enzymes are capable of existing in higher states of aggregation than the enzyme from animal sources.…”
Section: Discussionsupporting
confidence: 67%
“…The mol wt of this form is in close accord with the reported mol wt of NAD malic enzyme isolated from animal sources (7,12). Mol wt of approximately 300,000 to 400,000 have been reported for impure preparations of NAD malic enzyme from plant tissues (4,10,14). As we also find that the purified NAD malic enzyme from potato can exist in a higher mol wt form (477,000 D) it would seem that the plant NAD malic enzymes are capable of existing in higher states of aggregation than the enzyme from animal sources.…”
Section: Discussionsupporting
confidence: 67%
“…In addition to the NAD malic enzyme, enzymes which produce pyruvate from malate using NADP as a cofactor have been reported from plant sources (7,8,15). We have found that the oxidation of malate by extracts of sweet potato mitochondria using NADP as a cofactor is somewhat variable, but in several different preparations, the activity with NADP was found to be 16.4 ± 1.5% of the activity with NAD.…”
Section: Resultsmentioning
confidence: 80%
“…The NAD malic enzyme has been isolated from a number of plant mitochondria (3,8,9,14,15 (8,9) also seems to indicate the probable importance of its role as part of a crucial switching point in plant metabolism.…”
Section: Resultsmentioning
confidence: 96%
“…Enzymes implicated in synthesis and catabolism of this substrate are widely distributed in the cellular compartments. If these enzymes have become well known in herbaceous plants (Macrae, 1971;Davis and Patil, 1975;Wiskich and Dry, 1985;Artus and Edwards, 1985), very few studies have been made on woody plants Cheliak, 1985, 1986;Weimar and Rothe, 1987 (Gerant et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Enzymatic activities were measured according to Hatch (1978) for fumarase (EC 4.2.1.2), Davis and Patil (1975) for NADmalic enzyme (EC 1.1.1.39), Queiroz (1968) (Fig. 1A) and June 1987-March 1988 for spruce (Fig.…”
Section: Introductionmentioning
confidence: 99%